1999
DOI: 10.1159/000054112
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Heparin for Treating Human Malignancies

Abstract: There is a substantial amount of data implicating coagulation mechanisms in the pathogenesis of malignancy. Studies in some experimental animal models have shown that the anticoagulant heparin limits tumour growth and metastasis and prolongs survival. Experience with the effects of heparin on human malignancy is limited primarily to settings in which it was given either to prevent or to treat thrombosis in patients who also had cancer. However, these studies have shown noteworthy apparent improvement in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 67 publications
0
28
0
2
Order By: Relevance
“…[9][10][11][12]. A few clinical trials also suggested a beneficial effect of heparin in humans with cancer (13)(14)(15)(16)(17). However, heparin therapy can be difficult to manage on an outpatient basis and is associated with some complications.…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12]. A few clinical trials also suggested a beneficial effect of heparin in humans with cancer (13)(14)(15)(16)(17). However, heparin therapy can be difficult to manage on an outpatient basis and is associated with some complications.…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
“…Meanwhile, other studies showed that heparin is not just an anticoagulant, but a complex set of multifunctional glycosaminoglycan molecules with many other potential biological effects (24)(25)(26). Thus, several other explanations for the heparin effect on cancer have been suggested, including modulation of growth factors, inhibition of angiogenesis via interactions with vascular endothelial growth factors, and inhibition of the heparanases thought to be required for tumor cells to invade the vascular basement membrane (10,16,24,(27)(28)(29). Indeed, recent studies indicate that several anionic molecules that inhibit heparanases can diminish metastasis (28,29).…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42][43]. The glycosaminoglycan heparin, which is clinically used as an anticoagulant, is known to inhibit tumor growth and metastasis (44)(45)(46)(47)(48). Heparin also is a potent inhibitor of P-and L-selectin (49,50).…”
mentioning
confidence: 99%
“…Thromboprophylaxis with unfractionated heparin and low-molecular weight heparin (LMWH) has been used for management of hypercoagulable state in cancer patients, and LMWH is the recommended anticoagulant regimen by international guidelines [1,2]. Many retrospective analyses of clinical data indicated that heparin treatment affects survival of cancer patients with various tumors, especially in patients with the early stage of a disease [3][4][5]. Based on these observations several prospective clinical trials has been performed to evaluate heparins for its anticancer potential [6][7][8][9][10][11][12][13][14].…”
Section: Heparin Affects On Cancer: Clinical Evidencementioning
confidence: 99%